Risk and prognosis of secondary bladder cancer after radiation therapy for pelvic cancer - Li, Shuofeng; Wei, Ran; Yu, Guanhua; Liu, Hengchang; Chen, Tianli; Guan, Xu; Wang, Xishan; Jiang, Zheng (Frontiers in Oncology, 2022)
Background: Radiation therapy (RT) is a crucial modality for the local control of pelvic cancer (PC), but the effect of pelvic RT on the development of secondary malignancy is still unclear. This study aimed to identify the relationship between radiation therapy received for the treatment of primary PC and subsequent secondary bladder cancer (SBC). Methods: The Surveillance, Epidemiology, and End Results (SEER) database (from 1975 to 2015) was queried for PC. Fine-gray competing risk regression and Cox regression analyses were employed to assess the cumulative incidence of SBC. Poisson regression and multiple primary standardized incidence ratios (SIR) were used to evaluate the radiotherapy-associated risk for patients receiving RT. Subgroup analyses of patients stratified by latency time since PC diagnosis, calendar year of PC diagnosis stage, and age at PC diagnosis were also performed. Overall survival (OS) was compared among different treatment groups with SBC by Kaplan–Meier analysis. Results: A total of 318,165 observations showed that the primary cancers were located in pelvic cavity , 256,313 patients did not receive radiation therapy (NRT), 51,347 patients who underwent external beam radiation therapy (EBRT), and 10,505 patients receiving a combination of EBRT and brachytherapy (EBRT–BRT) who developed SBC. Receiving two types of radiotherapy was strongly consistent with a higher risk of developing SBC for PC patients in Fine-Gray competing risk regression (NRT vs. EBRT, adjusted HR= 1.71, 95% CI: 1.54-1.90, P＜0.001; NRT vs. EBRT–BRT, adjusted HR= 2.16, 95% CI: 1.78-2.63, P＜0.001). The results of the dynamic SIR and Poisson regression analysis for SBC revealed that a slightly increased risk of SBC was observed after RT in the early latency and was significantly related to the variations of age at PC diagnosis and decreased with time progress. For overall survival, the SBC after NRT, SBC after EBRT, and SBC after EBRT-BRT of 10-year survival rates were 37.9%, 29.2%, and 22.2%, respectively. Conclusion: Radiotherapy for primary pelvic cancers was associated with higher risks of developing secondary bladder cancer than patients unexposed to radiotherapy. Different pelvic RT treatment modalities had different effects on the risk of SBC.